ANALISIS STRUKTUR KOMUNITAS DIATOM PLANKTONIK DI PERAIRAN PULAU TOPANG KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Roito, Martin; Siregar, Yusni Ikhwan; Mubarak, Mubarak (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
This research was conducted in December 2013 at Topang island waters, Meran-ti Islands Regency, Riau Province. The study observed the structure of planktonic di-atoms community as well as the nitrate and phosphate concentrations of its adjacentwater. Four blocks were established during the study which located on the west, east,north and southern part of the island. The study recorded 5 genera of centrales diatomsand 4 genera of penales diatoms. The nitrate concentration ranged from 0.118 – 0.287ppm, while phosphate concentration ranged from 0.049 – 0.142 ppm. The highestabundance of diatom was founded in the west site of Topang island (1582.25 ind/L)and the lowest was in southern site of Topang island (969.41 ind/L). Chaetoceros andNitzschia were appeared as with the highest abundance. The study concluded thatTopang waters were categorized as oligotrophic waters.